US NATIONAL DEBT - Norboyev Tura (European Science Publishing, 2025)
As the world's largest economy, the United States plays an important role in shaping international financial markets and influencing global economic trends. Therefore, public debt management in the United States is a matter of paramount importance not only for the country itself, but also for the stability and functioning of the global economy, including the economy of Uzbekistan.
Keywords: Debt, economic stability, economy, GDP, national debt.